Comparative transcriptomic analysis of mouse macrophages infected with live attenuated vaccine strains of Mycobacterium tuberculosis - Veerapandian, Raja; Yang, Barbara; Carmona, Areanna; Sedano, Melina J.; Reid, Victoria; Jimenez, Rodrigo; Chacon, Jessica; Jagannath, Chinnaswamy; Ramos, Enrique I.; Gadad, Shrikanth S.; Dhandayuthapani, Subramanian (Frontiers in Immunology, 2025)
The BCG vaccine has been used against tuberculosis (TB) for over a hundred years; however, it does not protect adults from pulmonary TB. To develop alternative vaccines against TB, we generated Mycobacterium tuberculosis H37Rv (Mtb)-derived vaccine strains by rationally deleting key virulent genes, resulting in single (SKO; ΔfbpA), double (DKO; ΔfbpA-ΔsapM), triple (TKO-D; ΔfbpA-ΔsapM-ΔdosR and TKO-Z; ΔfbpA-ΔsapM-Δzmp1), and quadruple (QKO; ΔfbpA-ΔsapM-Δzmp1-dosR) strains. To understand how macrophages, the host cells that defend against infection and process antigens for presentation to immune cells, respond to these vaccine strains, we performed transcriptomic analyses of mouse bone marrow-derived macrophages (BMDMs) infected with these strains. The transcriptomic data were compared with similar data obtained from macrophages infected with Mtb H37Rv and BCG. Our analyses revealed that genes associated with various immune and cell signaling pathways, such as NF-kappa B signaling, TNF signaling, cytokine-cytokine receptor interaction, chemokine signaling, hematopoietic cell lineage, Toll-like receptor signaling, IL-17 signaling, Th1 and Th2 cell differentiation, Th17 cell differentiation, and T cell receptor signaling were differentially expressed in BMDMs infected with our vaccine strains. Enhanced expression of cytokines and chemokines, including proinflammatory cytokines such as TNF-α, IL-6, GM-CSF, and IL-1, which are essential for the immune response against Mtb infection, was also observed in BMDMs infected with these strains. In particular, BMDMs infected with all vaccine strains exhibited a significant upregulation of genes associated with the IL-17 pathway. These results may indicate that our vaccine strains could induce a protective immune response against TB.